Efeito da temperatura de síntese do nitreto de carbono (g-C3N4) na degradação fotocatalítica da rodamina B - Matos, Maria Angelica Freitas (2022)
Pollution of water bodies is a problem of great relevance, considering that it affects human health and exacerbates water scarcity. In particular, pollution caused by dyes is of concern due to the stability and toxicity of these substances. In this context, photocatalysis emerges as an efficient technology to degrade these organic compounds, converting them into CO2 and H2O. Thus, in this work, g-C3N4 (carbon nitride) photocatalysts were prepared at different temperatures (350 °C, 400 °C, 450 °C, 500 °C and 550 °C), using urea as a precursor. The catalysts obtained were characterized by scanning electron microscopy, Fourier transform infrared spectroscopy, thermogravimetric analysis, zeta potential measurements and UV-Vis diffuse reflectance spectroscopy and their performance was evaluated in the photodegradation of Rhodamine B under visible and UV light. The characterization results demonstrated that incomplete polymerization of urea occurs at temperatures below 450 ºC and showed an increase in the polymeric network of g-C3N4 with the increase in the temperature of synthesis. Photocatalytic assays indicated that the degradation efficiency of Rhodamine B depends on the synthesis temperature and the light source used. Materials calcined at 400°C and 550°C showed better photocatalytic performance under UV light and visible light, respectively. The generation mechanism of the reactive species involved in the degradation of Rhodamine B for the materials was investigated, with the valence band holes having a major contribution in the studied photocatalytic reaction.